Geographic regulation and cooperative investment in next generation broadband networks - Roberto E. Balmer (International Telecommunications Society (ITS), 2014)
Alternative telecommunications operators have continuously invested in their own infrastructure in recent years. After more than a decade since liberalization, competitive conditions have substantially changed, especially in urban areas. European regulatory authorities have acknowledged this development by starting regional deregulation. Additionally, different forms of cooperative investments in next generation broadband have appeared on the market. The effects of such schemes on competition, investment and welfare crucially depend on the fine details of implementation. For instance, in the case of joint ventures, it matters how investment costs are shared and how internal and external access prices are determined. In the case of long-term access agreements, it is essential to consider how access tariffs are structured, whether they can adapt to market developments ex-post and whether contracts are signed before or after the investment takes place. Generally, many of these agreements allow some extent of risk sharing, offering the possibility to increase investment incentives when firms are not risk neutral. This article reviews the theoretical and empirical literature on geographic regulation and co-investments in next generation broadband. It is suggested that regulators consider introducing regulated co-investment agreements complementing current regulation or in some cases even substituting for it, in addition to considering geographically segmented access prices.
Keywords: 330; next generation access; co-investment models; cooperative investment; investment sharing; investment cooperation; geographic regulation